Gadamer’s Question to History - Dubnikas, Kęstutis (Problemos, 2003)
The article is intended as Gadamer’s hermeneutic criticism of the science of history. The problem is raised from a methodological perspective: do arguments of ontological historicity question historical reflection? The article tackles a correlation among three ways to perceive history: everyday conscious, critical approach to the science of history and a hermeneutical understanding. The latter restores to critical analysis what has been neglected in it, i.e., preconceptual experience. It is demonstrated that the opposition of hermeneutical understanding to methodic historical consciousness transfers the issue of knowledge of history to the domain of historically conditioned paradigms.